Imaging for Diagnosis and Monitoring of Cardiac Sarcoidosis - Mehdipoor, Ghazaleh; Bokhari, Sabahat; Prince, Martin R. (International Journal of Cardiovascular Practice, 2018)
Sarcoidosis is a granulomatous condition, primarily affecting the lungs and thoracic lymph nodes. Clinical cardiac involvement might occur in 2 to 5% of patients with sarcoidosis, and can be associated with serious complications including heart block, cardiomyopathy, ventricular arrhythmias, and potentially death. Timely diagnosis helps initiate treatment before cardiac damage becomes irreversible. In this brief review, we discuss imaging updates for diagnosis and monitoring of cardiac sarcoidosis.